Fundamental motor skills of kindergarten children in different environments and ethnic groups in Northwest China - Xiaohui Xia; Liang Chao; Chen Nan; Xuejuan Yin; Huifang Zheng; Sheping Zhang (BMC, 2022)
Abstract Background The status of children's early motor skills play an important role during childhood and across lifetime. This study described FMS proficiency among boys (n = 189) and girls (n = 179) kindergarten children from 3 to 6 years old (4.4 s 0.7, mean ± SD) in northwest China. The differences in FMS proficiency of boys and girls from different environments, ethnic groups were analyzed respectively. Methods TGMD-3 was used to assess FMS. FMS mastery level was defined according to the correct performance of all criteria over two trials. The correlation between BMI and FMS and the interaction of environmental and ethnic on FMS were analyzed. The general linear model was used to evaluate the differences of boys and girls among environment groups (urban/suburban/county), and ethnic groups (Han/Hui/Tibetan) on the FMS subsets respectively. Results FMS proficiency was assessed in 368 3- to 6-year-old children (n = 156 urban, n = 101 suburban, n = 111 county)/(n = 208 Han, n = 107 Hui, n = 53 Tibetan). Overall, the highest skill performance was the run, with 86% achieving mastery level, and the poorest performance was the FH strike, at only 19%. Correlation between BMI and FMS is minimal. According to TGMD-3 scores, there was no significant difference between boys and girls in total FMS (p = 0.38). In terms of locomotor skills, boys performed better than girls in the hop, skip and slide (p < 0.05). County children performed significantly difference than urban and suburban children. Some skills performed less proficiently, (boys in 6 of 13 skills: run, HJ, slide, TH strike, FH strike and kick; girls in 4 of 13 skills: run, slide, TH strike and kick) and some skills performed more proficiently (boys in dribble; girls in hop and dribble). Tibetan children performed significantly difference than Han and Hui children. Some skills performed less proficiently, (boys in 6 of 13 skills: run, HJ, slide, TH strike, FH strike and kick; girls in TH strike) and some skills performed more proficiently (boys and girls were all in dribble). Conclusion Children in northwest China showed certain characteristics in FMS, the county/Tibetan boys and girls performed poorer than others in ability to execute particular process characteristics of some skills and performed more outstanding in other skills. It suggests that a certain group population may need specific focus on interventions to improve their FMS level.